Hardness testing machine with detection structure for testing hardness of rubber material of machine - ZHANG CAI (2021)
The utility model discloses a hardness testing machine with a detection structure for testing machine rubber material hardness, which comprises a working table, a hardness testing machine is arranged in the middle of the top of the working table, a limiting sliding groove is formed in the inner bottom wall of the hardness testing machine, a limiting sliding block is connected in the limiting sliding groove in a sliding mode, and the limiting sliding block is connected with the working table in a sliding mode. A placing table is arranged at the top of the limiting sliding block, a protection frame is arranged in the middle of the top of the placing table, and a lead screw penetrates through the surface of the protection frame. Through the arrangement of the limiting sliding groove, the limiting sliding block, the placing table, the lead screw, the arc-shaped clamp and the non-slip mat, a rubber material is placed on the placing table, the tested rubber material is clamped by rotating the lead screw and the arc